Boosting life sciences research in Brazil: building a case for a local Drosophila stock center - Oliveira, Marcos T. [UNESP]; Anhezini, Lucas; Araujo, Helena M.; Oliveira, Marcus F.; Couto-Lima, Carlos A. [UNESP] (FapUNIFESP (SciELO), 2024)
Drosophila melanogaster is undoubtedly one of the most useful model organisms in biology. Initially used in solidifying the principles of heredity, and establishing the basic concepts of population genetics and of the synthetic theory of evolution, it can currently offer scientists much more: the possibility of investigating a plethora of cellular and biological mechanisms, from development and function of the immune system to animal neurogenesis, tumorigenesis and beyond. Extensive resources are available for the community of Drosophila researchers worldwide, including an ever-growing number of mutant, transgenic and genomically-edited lines currently carried by stock centers in North America, Europe and Asia. Here, we provide evidence for the importance of stock centers in sustaining the substantial increase in the output of Drosophila research worldwide in recent decades. We also discuss the challenges that Brazilian Drosophila scientists face to keep their research projects internationally competitive, and argue that difficulties in importing fly lines from international stock centers have significantly stalled the progression of all Drosophila research areas in the country. Establishing a local stock center might be the first step towards building a strong local Drosophila community that will likely contribute to all areas of life sciences research.
Keywords: developmental biology; Genetically-defined lines; mitochondrial metabolism; neurobiology; quantitative genetics